NOTE ON ORGANIC COMPOSITION OF MUSCLE OF SOME EDIBLE FRESHWATER ANIMALS - Janakiram, B; Venkateswarlu, Y; Reddy, G Rajarami; Babu, K Sasira (Indian Journal of Fisheries, 2011)
High protein and lipid levels were noticed in the muscle of prawn, fish and frog, while the carbohydrate, free fatty acid and glycogen levels were high in frog and snail